Thermogravimetric and mass spectrometric (TG-MS) analysis of sub-bituminous coal-energy crops blends in N2, air and CO2/O2 atmospheres. (1st March 2018) - Rodilla, I.; Contreras, M.L.; Bahillo, A.
Highlights: Coal combustion improved when it's blended and occurs in oxyfuel atmospheres. Biomass presence seems to increase the reactivity of the samples. An increase of activation energy was described when biomass share increased. HCl presence is higher when the percentage of biomass increased. Abstract: During oxy-fuel combustion, the gas composition inside the boiler differs from that of conventional combustion in air, which affects to different aspects in combustion processes. Besides, the need to increase the efficiency in energy production in a sustainable way leads to increasingly extreme conditions imposing more demanding performances on materials such as higher temperatures and pressures in more corrosive environments. The scope of this work is to understand the thermal behaviour and the kinetic of an energetic crop with high chlorine content blended with a Spanish coal at different atmospheres with special attention to oxyfuel combustion conditions and to determine the formation of those compounds which may induce corrosion, by means of mass spectrometry analysis. The addition of biomass to the fuel mixture seems to increase the reactivity of the samples. The rate maximum of mass change increases with the oxygen content reaching values from 13.6, 16 and 17.7%/min with N2, air and oxyfuel atmosphere respectively using 100% of cynara as fuel. The greater reactivity of the oxygen decreases the peak temperature being about 325 °C with N2, 309 °C with air and 304 °C at oxyfuel conditions. The activation energy increased when the biomass share in the blend independently of the atmosphere and the heating rate. The activation energy is similar to combustion and oxyfuel combustion conditions but about 5–7 kJ/mol higher than pyrolysis atmosphere for all biomass mixture studied. The optimal blend based on the lowest activation energy is 20:80% of cynara/coal. HCl presence is higher when the percentage of biomass increased. However, SO2 presence is more related with coal presence. It is important to stand out that any percentage of cynara in the mixture shift to lower temperatures the SO2 emission profile, from 500 °C to 300 °C. This fact is also observed in the curves of the weight loss derivative.